2013
DOI: 10.1089/aid.2013.0069
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Aging Not Gender Is Associated with High Atazanavir Plasma Concentrations in Asian HIV-Infected Patients

Abstract: Physiological effects of aging make the older population more susceptible to adverse drug events and drug-drug interactions. We evaluated the impact of aging and gender on the pharmacokinetics (PK) of atazanavir/ritonavir (ATV/r) 300/100 mg once daily (qd) in 22 well-suppressed HIV-infected patients. This was a 24-h intensive PK study. Subjects were HIV-1-infected adults aged ‡ 18 years with HIV RNA < 50 copies/ml and treated with ATV/r 300/100 mg once daily plus two nucleoside reverse transcriptase inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
1
7
1
Order By: Relevance
“…In a study evaluating trough concentrations measured during therapeutic drug monitoring, their analysis suggested no changes in EFV concentrations with age, with increased concentrations of protease inhibitors, such as ATV and RTV, although only 16.5% of these participants were 50 years old or older 37. In a noncompartmental analysis of ATV/RTV PK in Thai patients with HIV, age >42 years was found to be significantly associated with increased ATV and RTV area under the curve and peak plasma concentration (C max ), however, the median age in this study was 42 years and the oldest subject was 57 years old 38. In the present work, 38% of EFV and 36% of ATV/RTV participants were 50 years of age or older, with the oldest subject in each group 73 and 61, respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…In a study evaluating trough concentrations measured during therapeutic drug monitoring, their analysis suggested no changes in EFV concentrations with age, with increased concentrations of protease inhibitors, such as ATV and RTV, although only 16.5% of these participants were 50 years old or older 37. In a noncompartmental analysis of ATV/RTV PK in Thai patients with HIV, age >42 years was found to be significantly associated with increased ATV and RTV area under the curve and peak plasma concentration (C max ), however, the median age in this study was 42 years and the oldest subject was 57 years old 38. In the present work, 38% of EFV and 36% of ATV/RTV participants were 50 years of age or older, with the oldest subject in each group 73 and 61, respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…Moreover, 91% of the older subjects vs . 36% of the younger subjects had atazanavir C trough higher than the proposed upper limit for toxicity (0.85 mg/L), and the multivariate analysis found older age to be the only significant predictor for high atazanavir concentrations .…”
Section: Discussionmentioning
confidence: 78%
“…The geometric mean plasma C trough of darunavir and ritonavir was significantly higher in older subjects than in younger individuals, while the geometric mean plasma C trough of raltegravir was comparable between older and younger subjects. This increase in plasma concentrations of protease inhibitors in elderly people is comparable to that observed in other studies , and probably arises from pharmacokinetic changes which physiologically occur in older subjects, leading to a slower clearance of several drugs. However, raltegravir showed comparable plasma levels in younger and older subjects, as reported by other authors , and its metabolism and excretion are probably less affected by the pharmacokinetic changes occurring in older people.…”
Section: Discussionmentioning
confidence: 96%
“…Three prospective studies assessing the PK effects of ARVs in older HIV‐infected patients were identified . A study evaluated the exposure of two alternative first‐line regimens in 12 HIV‐infected adults aged 55 years or older (mean age 59.7 ± 3.9 yrs) in an unblinded, intensive‐sampling PK study.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…A groups of investigators evaluated the impact of age and gender on the PK of atazanavir (300 mg/day), ritonavir (100 mg/day), and two NRTIs (once/day) in a 24‐hour intensive PK study. Twenty‐two HIV‐infected adults were included and received ART for at least 2 weeks prior to the start of the study.…”
Section: Pharmacokineticsmentioning
confidence: 99%